XPS analysis of damp heat aged and fractured polymer/glass laminates - Gary Säckl; Gernot M. Wallner; Jiri Duchoslav; Martin Tiefenthaler; David Stifter (Polymer Testing, 2024)
Essential for the durability of photovoltaic (PV) modules is the polymeric encapsulant. In addition to the well-established ethylene vinyl acetate copolymers (EVA), polyolefin elastomers (POE) are gaining market relevance. The main objective of this paper was to elucidate the ageing and degradation mechanisms of PV relevant glass laminates based on UV-transparent EVA and POE encapsulants by X-ray photoelectron spectroscopy (XPS).Special focus was given to the polymer/glass interfaces. Therefore, glass laminates were damp heat aged and debonded by monotonic compressive shear testing. Subsequently, the polymer side of the fractured surfaces was characterized by XPS and Fourier-transform infrared spectroscopy (FTIR). The polar EVA encapsulant revealed more pronounced deterioration than the less polar POE material.Significant differences were already discernible after 1kh of damp heat exposure. The diffusion of Na ions from the glass substrate into the polymer matrix and the formation of Na salts at the interface were ascertained for EVA and to a less extent also for POE. While EVA laminates failed primarily close to the interface, but still within the EVA material, glass residues were detected on the fractured POE surfaces indicating interface-near glass corrosion and a fracture path propagating back and forth within POE and glass.